Factor affecting the use of e-money in millennial generation: Research model UTAUT 2 - Lizar Alfansi; Muhammad Yasser Iqbal Daulay (Jurnal Manajemen dan Pemasaran Jasa, 2021)
This study aims to determine the factors that influence users in using electronic money in transactions. The Unified Theory of Acceptance and Use of Technology (UTAUT) is used as a research model with independent variables: performance expectations, facility conditions, social influence, expectations, perceived values, habits, beliefs, and hedonic motivation. The dependent variable in this study is actual use and interest to be used as a mediator variable. This research method uses an online survey method that is distributed using Google Surveys. This study's sample was 194 electronic money users spread across three major cities in Indonesia, such as DKI Jakarta, West Java, and Central Java. Primary data collected were analyzed using SmartPLS software. The study results explain that trust is a substantial factor in influencing the use of electronic money. Companies, in this case, must pay attention to system security factors to be able to attract millennials using electronic money.